Antibodies Reactive to Commensal Streptococcus mitis Show Cross-Reactivity With Virulent Streptococcus pneumoniae Serotypes - Shekhar, Sudhanshu; Khan, Rabia; Ferreira, Daniela M.; Mitsi, Elena; German, Esther; Rørvik, Gro Herredsvela; Berild, Dag; Schenck, Karl; Kwon, Keehwan; Petersen, Fernanda (Frontiers in Immunology, 2018)
Current vaccines against Streptococcus pneumoniae, a bacterial species that afflicts people by causing a wide spectrum of diseases, do not protect against all pneumococcal serotypes. Thus, alternative vaccines to fight pneumococcal infections that target common proteins are under investigation. One promising strategy is to take advantage of immune cross-reactivity between commensal and pathogenic microbes for cross-protection. In this study, we examined the antibody-mediated cross-reactivity between S. pneumoniae and S. mitis, a commensal species closely related to S. pneumoniae. Western blot analysis showed that rabbit antisera raised against S. mitis reacted with multiple proteins of virulent S. pneumoniae strains (6B, TIGR4, and D39). Rabbit anti-S. pneumoniae IgG antibodies also showed binding to S. mitis antigens. Incubation of rabbit antisera raised against S. mitis with heterologous or homologous bacterial lysates resulted in marked inhibition of the developments of bands in the Western blots. Furthermore, serum IgG antibodies from adult human volunteers intranasally inoculated with S. pneumoniae 6B revealed enhanced S. mitis-specific IgG titers compared to the pre-inoculation samples. Using an on-chip protein microarray representing a number of selected membrane and extracellular S. pneumoniae proteins, we identified choline binding protein D (CbpD), cell division protein (FtsH), and manganese ABC transporter or manganese-binding adhesion lipoprotein (PsaA) as common targets of the rabbit IgG antibodies raised against S. mitis or S. pneumoniae. Cumulatively, these findings provide evidence on the antibody-mediated cross-reactivity of proteins from S. mitis and S. pneumoniae, which may have implications for development of effective and wide-range pneumococcal vaccines.